British naval aviation the first 100 years - Benbow, Tim (Corbett Centre for Maritime Policy Studies series, 2011)
In 1909 the British Admiralty placed an order for a rigid airship, marking the beginning of the Royal Navy's involvement with airpower. This collection charts the Navy's involvement with aviation over the following century, and the ways in which its rapid expansion and evolution radically altered the nature of maritime power and naval strategy. Drawing on much new historical research, this collection takes a broadly chronological approach which allows a scholarly examination of key themes from across the history of British naval aviation. The subjects tackled include long-standing controversies over the control of naval air power, crucial turning points within British defence policy and strategy, the role of naval aviation in limited war, and discussion of campaigns - such the contribution of the Fleet Air Arm in the Mediterranean and Pacific theatres of the Second World War - that have hitherto received relatively little attention. This collection concludes with a discussion of recent debates surrounding the Royal Navy's acquisition of a new generation of carriers, setting the arguments within an historical context. Taken as a whole the volume offers fascinating insights into the development of a key aspect of naval power as well as shedding new light on one of the most important aspects of Britain's defence policy and military history. By simultaneous addressing historical and current political debates, it is sure to find a ready audience and stimulate further discussion.